Excess Savings Are Recession-Specific and Compensatory: Evidence From the US - Liviu Voinea; Prakash Loungani (Intereconomics)
Abstract There is a consensus among academics and policymakers that the excess savings built up by households during the past couple of years are specific to the pandemic. Based on data from the past half century for the US, this article shows that savings generally increase during recessions; the pandemic is different only by the magnitude of these savings, but not by their sign. Moreover, it suggests that these excess savings are rather compensatory than precautionary, as households save more to rebuild their lost wealth.